Energy-efficient green synthesis of metal-organic frameworks for effective electrochemical nitrite sensing - Amali, R.K.A.; Lim, H.N.; Ibrahim, I.; Zainal, Z.; Ahmad, S.A.A. (Elsevier, 2023)
This paper describes a green method for synthesizing a metal-organic framework (MOF) based on pyrazole-3,5- dicarboxylic acid (H3PDCA) linker and Ni2+ to detect nitrite electrochemically. The synthesis was performed at room temperature using water as a solvent, and physicochemical and electrochemical characterizations confirmed the successful creation of Ni-PDCA. The study findings underline that the Ni-PDCA exhibited excellent electrochemical performance for nitrite oxidation due to the appreciable conductivity and high electroactive surface area offered by polyhedral Ni-PDCA crystals. In addition, the charge transfer mechanism between nitrite and the ligand contributed to the selective detection of nitrite. Under optimum amperometric settings (0.70 V vs. Ag/AgCl), Ni-PDCA-modified screen-printed carbon electrode (SPCE) exhibited a detection limit of 0.052 µM (S/ N = 3) with a sensitivity of 240 µA mMˆ’ 1 cmˆ’ 2 in a linear range of 0.1 to 1000 µM. Moreover, the sensor provided good selectivity, high stability (> 28 days), and a fast response time (< 5 s). Remarkable repeatability Relative standard deviation (RSD) = 0.87%, n = 10 and reproducibility RSD = 0.67%, n = 4 were other advantages of this sensor. Notably, the evaluation of nitrite in tap water samples confirmed that the Ni-PDCA/ SPCE has promising prospects in quantitatively detecting nitrite in real samples. Therefore, this study paves the way for a practical, cost-effective, and eco-friendly electrochemical sensing method for nitrite detection.